mFAST: A MATLAB toolbox for ocean bottom seismometer refraction first-arrival traveltime tomography - Bin Liu (Earth and Planetary Physics, 2022)
First-arrival seismic traveltime tomography (FAST) is a well-established technique to estimate subsurface velocity structures. Although several existing open-source packages are available for first-arrival traveltime tomography, most were written in compiled languages and lack sufficient extendibility for new algorithms and functionalities. In this work, we develop an open-source, self-contained FAST package based on MATLAB, one of the most popular interpreted scientific programming languages, with a focus on ocean bottom seismometer refraction traveltime tomography. Our package contains a complete traveltime tomography workflow, including ray-tracing-based first-arrival traveltime computation, linearized inversion, quality control, and high-quality visualization. We design the package as a modular toolbox, making it convenient to integrate new algorithms and functionalities as needed. At the current stage, our package is most efficient for performing FAST for two-dimensional ocean bottom seismometer surveys. We demonstrate the efficacy and accuracy of our package by using a synthetic data example based on a modified Marmousi model.